WHAT LITERATI TALKED ABOUT WHEN THEY TALKED ABOUT MEMORY: COMMEMORATING RESISTANCE TO THE TAIPING IN NANJING'S YU GARDEN, 1900–1911. (January 2015) - W, C
Abstract : As used in current scholarship, the term "memory" encompasses much more than the recollections of particular people. It considers the totality of practices that people use to record and transmit information about the past. This memory scholarship rarely considers the ways particular historical actors have used the word "memory." This article is a case study of one group of degree holders in Nanjing who gathered in a garden to commemorate an 1854 plot against the Taiping. Their writings addressed the virtue they thought surrounded them. When they spoke of memory, their main concern was not so much the loss of the war, or even the loss of the memory of the war, but rather the loss of the cultural value placed on people who remember, which for them would mean the end of the literati class as they knew it. Local commemorative practices thus expressed a deeper anxiety that was articulated in the language of memory.